Cellular proteins specifically bind single- and double-stranded DNA and RNA from the initiation site of a transcript that crosses the origin of DNA replication of herpes simplex virus 1. - Roller, R J (1989)
The small-component origins of herpes simplex virus 1 DNA synthesis are transcribed late in infection by an RNA with heterogeneous initiation sites approximately 290-360 base pairs from the origins. We report that cellular proteins react with a labeled RNA probe representing the 5' terminus of a subset of this RNA but not with the complementary strand of this RNA. The proteins form two complexes. Complex 2 was formed by all nuclear extracts tested, whereas complex 1 was invariably formed by proteins present only in nuclear extracts of mock-infected cells. Complex 1 protects a contiguous stretch of 40 nucleotides of the labeled RNA probe from nuclease degradation. Formation of complex 1 was competitively inhibited in a sequence-specific fashion by single-stranded RNA and DNA and by double-stranded RNA and DNA. The protein(s) forming complex 1 is, thus, quite distinct from known nucleic acid-binding proteins in that they recognize a specific nucleotide sequence, irrespective of the nature (single- and double-stranded RNA and DNA) of the nucleic acid. We conclude the following: (i) the proteins forming complex 1 and 2 are probably different, (ii) complex 1 is neither required throughout infection for viral replication nor able to hinder viral replication in cells in culture, and (iii) cells susceptible to infection encode one or more proteins that recognize specific sequences in single-stranded nucleic acids; either these proteins impart a compatible conformation on single-stranded nucleic acids with the conformation of the same strand in the double-stranded nucleic acid, or these proteins confer a specific, distinct conformation to both single-stranded and double-stranded nucleic acids.